Nutrition and wound healing - Molnar, Joseph Andrew (CRC Press/Taylor & Francis Group, 2006)
With mounting evidence regarding the role of poor nutrition in the development of chronic diseases such as heart disease and diabetes, it is no secret that appropriate nutrition is crucial to optimal health. Achieving the correct balance of elements provides the body with the ability to adapt to a shifting and often hazardous environment. Never is this capability more important than when a wound is sustained and the body's first line of defense, the skin, is breached.Nutrition and Wound Healing describes the importance of several nutrients, both macronutrients and micronutrients. - Resumé vydavatel
Description based upon print version of record.
Keywords: terapie ran; hojení ran; nutriční terapie; wound therapy; wound healing; nutritive therapy; elektronické knihy; kolektivní monografie; electronic books; collective monographs